ANALISIS SEMIOTIKA REPRESENTAMEN PADA NOVEL HALLOWEâ€™EN PARTY KARYA AGATHA CHRISTIE - SUMENDAP, VICHA CLAUDIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study entitiles â€œAnalisis Semiotika Representamen dalam Novel Halloweâ€™en Party Karya Agatha Christieâ€. Semiotis is a study about signs. The Representamen signs is one of the triadic concepts. Daily activity can be divided into Representamen signs. This study is an attempt to identify, classify, and analyze the sign of Representamen contained in the novel. The data are collected through the writerâ€™s explanation about the Representamen as a conduit of information. The writer uses theory of Peirce to identify and classify the data. In analyzing the data, the writer used the theory of Bathes which states that connotation is a new meaning that gives user the sign in accordance with wishes, background of knowledge, or a new convention that exists in a society. The results of this theory show that based on the theory of Peirce there are three form of Representamen contained in the novel. Those are Qualisgn, Sinsign, and Legisign. The meanings contained in the sign of Representamen are so many such as thinking, caring, confusion, frustration, fear, worry, affection, doubt, murderer, feeling guilty, shockness, warning and anger. The writer hopes that this study will hep the reader in understanding about semiotic study especially Representamen as one of the triadic concept and how it works in life. Â Keywords : Semiotics, Representamen, triadic concept, Novel Halloweâ€™en Party Â